Crossing Industry Borders: German Manufacturers as Services Exporters - Markus Kelle (The Vienna Institute for International Economic Studies (wiiw), 2012)
German manufacturing firms increasingly engage in service trade activities. Micro-level data show that producer service exports of German manufacturers amounted to EUR 30 billion in 2005. In particular, construction, engineering and R&D services are exported. The machinery industries and automobile and chemicals producers dominate the overall pattern. The types of services exported vary strongly across industries. Furthermore, export activities are concentrated on a few large exporters. Service exports of advertising, data processing and R&D services are found to likely support foreign affiliates of firms. However, these headquarter services are only infrequently observable. Much more important are construction and engineering services exported by machinery firms. These might represent installation and maintenance services exported to complement the supply of machinery. Beyond the support of foreign production affiliates of firms, R&D services exports generally represent the transfer of knowledge and technology. These might be relevant also in R&D cooperations of firms or when firms have partnerships with foreign suppliers or buyers of intermediate products.
Keywords: D22; F14; F23; L80; 330; services exports; manufacturing sector; goods trade; multinational firms